The Relevance of Convict Punishment in Sukamiskin Class 1 Prison, Bandung - Seisabila, Runi Sikah; Susanti, Vinita (Indonesian Journal of Multidisciplinary Science, 2023)
The phenomenon in society when talking about the theme of prisons in Indonesia is focused on overcrowding imprisonment in Indonesia and is quite concerning when looking at prisoners who are not taken care of in prisons. However, this discussion does not apply to the situation of Class I Prison, Sukamiskin, Bandung which has complete facilities provided in the prison and the condition of prisoners who can be said to be prosperous. Therefore, the author will discuss the relevance of the punishment received by prisoners in Sukamiskin Class 1 Prison comparable or not to all the complete circumstances and facilities in Sukamiskin Class 1 Prison by seeing that the punishment can have a deterrent effect on the perpetrators, preventing the crime from happening again.